Policy Analysis of Budget Utilization in Stunting Programs Based on District Health Account - Yeri Sanjaya; Surna Lastri; Hermansyah Hermansyah (Indonesian Journal of Global Health Research, 2024)
Stunting, a chronic nutritional issue with significant impacts on the quality of human resources, remains a major health challenge in Indonesia. This study analyzes the policy on budget utilization for stunting programs based on the District Health Account (DHA) to enhance the effectiveness and efficiency of health financing. The research was conducted at the Aceh Jaya Health Office, Aceh Province, using a quantitative method with a comparative program evaluation approach. Data were collected through a review of stunting budget documents from 2017 to 2023 and direct observations of budget distribution. The findings reveal an increasing trend in the stunting budget since the implementation of the stunting reduction acceleration policy in 2020, peaking at IDR 5.316 billion in 2023. Prior to this policy, budget allocations were fluctuating and lacked clear priorities. The use of DHA provided a comprehensive overview of financial flows, funding sources, and their utilization. DHA also identified that most funds were allocated to indirect activities, such as maternal health management and community nutrition, while direct allocations for stunting patients tended to decrease. This study supports the effectiveness of DHA in optimizing budget allocation for stunting programs, ensuring more targeted use of funds, and improving financing efficiency. DHA has the potential to become a critical instrument for local governments in data-driven budget planning to achieve the national stunting prevalence target of 14% by 2024.